Fabrication and characterization of composite diamond like carbon films for some applications - Zhang, Ping (2008)
The filtered cathodic vacuum arc (FCVA) technique is powerful for thin film deposition. In this project, several sets of metal containing amorphous carbon (a-C:Me) films were successfully deposited, from metal/carbon composite targets, by using an FCVA system.